1990
DOI: 10.1111/j.1600-0714.1990.tb00805.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect on the incidence of oral submucous fibrosis of intervention in the areca nut chewing habit

Abstract: Incidence of oral submucous fibrosis was calculated from a 10-yr prospective intervention study of 12,212 individuals with a strong component of health education on tobacco and area nut chewing. Based on 11 new cases among 6341 chewers, the annual incidence was 8.0 per 100,000 among men and 29.0 for women. An earlier 10-yr follow-up study, with no intervention component, served as control. Based on 11 new cases among 3,809 chewers, the annual incidence was 21.3 per 100,000 for men and 45.7 for women controls. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(35 citation statements)
references
References 6 publications
2
33
0
Order By: Relevance
“…Some epidemiological surveys in India have shown a female predominance. 18,19 In our study, out of 50 OSMF patients, we observed 98% (n=49) were males and 2% (n=1) was female, which was similar to the study conducted by Chaturvedi VN et al 20 and Reddy V et al 7 in India. Male predominance in our study can be due to easy accessibility for use areca nut and its products more frequently than females in our society and changing lifestyles of the youngsters.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Some epidemiological surveys in India have shown a female predominance. 18,19 In our study, out of 50 OSMF patients, we observed 98% (n=49) were males and 2% (n=1) was female, which was similar to the study conducted by Chaturvedi VN et al 20 and Reddy V et al 7 in India. Male predominance in our study can be due to easy accessibility for use areca nut and its products more frequently than females in our society and changing lifestyles of the youngsters.…”
Section: Discussionsupporting
confidence: 79%
“…The reason attributes to the fact that the commercially available products are concentrated, freezes dried and have higher dry weight concentration of tobacco, areca nut, and slaked lime to the traditionally prepared home made products like panmasala. 19,22,23 Another factor supporting this could be the antioxidant capabilities of pan leaf which is known to be rich in beta-carotene, which has the capacity to quench free radicals that are mutagenic which counteracts the different pathology causing irritants. 24 In our study, as the duration of consuming habits increased above 3 years and frequency of habit of consuming for more than 5 times per day resulted in increased burning sensation of mouth and restricted mouth opening.…”
Section: Discussionmentioning
confidence: 99%
“…Our understanding of oral submucous fibrosis has evolved as a clinico-pathological entity over know of today [8][9][10][11][12][13][14][15] .…”
mentioning
confidence: 99%
“…The aetiology of OSMF is considered to be multifactorial (11), arecanut being the prime aetiology (12)(13)(14)(15). Occurrence of OSMF in cases without any history of using irritants, in teenagers, idiopathic nature of the disease and various immunological changes have led many researchers to consider OSMF as an autoimmune disorder (6,16).…”
Section: Introductionmentioning
confidence: 99%